The Reconstructed Child: The Psychoanalysis of the Autobiographical Works of Thomas Bernhard (Training and Practice : Journal of Educational Sciences, 2011)
This paper reviews the current research on narrative identity. Narrative identity has quickly become accepted as a promising process approach to self-development. This study tries to show contemporary theories on how early mother-child interactions build up the self; and traces the way how early experiences become transformed into narrative self. According to Winnicott there is a true and false self in everybody. Through this false self the infant builds up a false set of relationships. The primary function of the false self is defensive, to protect the true selffrom threat, wounding, or even destruction. This is an unconscious process. The psychoanalysis of Thomas Bernhard’s autobiographical work ’Gathering Evidence’ brings us closer to understand the process which forms the false self. Thomas Bernhard’s life was marked by recurrent misfortunes, including the humiliation of an illegitimate birth and a childhood spent in part with a mother who never disguised her contempt for him. One should not forget that Bernhard attempted a detailed portrayal of his own “biography” in the form of five autobiographical novels, which researchers have always seen as a mixture of poetry and truth.